Vocational or academic track? Study and career plans among Swedish students living in rural areas. (16th March 2018) - Rönnlund, Maria; Rosvall, Per-Åke; Johansson, Monica
ABSTRACT: This ethnographic study explores how rural lower secondary school students reflect on study and career choices, focusing on the choice between vocational and academic upper secondary programs. Applying a spatial perspective, we analyze individual students' reflections about study and career choices within a variety of rural regions, and compare patterns in the regions. The results indicate complex interactions between structural factors and individual dispositions. In places where education levels were low and the local labor market predominantly offered unskilled manual and service work, there was a stronger tendency to choose vocational programs than in places with higher education levels and access to a more varied labor market. Likewise, there was an association between strongly gendered labor markets and gender-typical choices. However, individual students positioned themselves actively in relation to the local place, its local labor market and social relations; their choices were place-bound to varying degrees, and chose upper secondary programs and presented ideas about prospective careers that were harmonious with the local labor market in some cases, but discordant in other cases. The results are discussed in the framework of individuals' horizon for actions.